2016
DOI: 10.1002/fam.2414
|View full text |Cite
|
Sign up to set email alerts
|

An international survey and full‐scale evacuation trial demonstrating the effectiveness of the active dynamic signage system concept

Abstract: Rapid evacuation from large buildings is challenging due to their complex layout making wayfinding difficult. While emergency signage is widely used to aid wayfinding, recent research demonstrates that only 38% of people perceive conventional exit signs. Furthermore, conventional signage only conveys single and passive information and so cannot adapt to changing conditions. The EU FP7 GETAWAY project addresses this problem through the development of a unique and innovative Intelligent Active Dynamic Signage Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…Studies on enhancing signage systems performance investigate the efficiency of signage systems according to the type, colour and design of the signage system [9,[16][17][18][19][20][21][22][23][24][25], and optimal installation location of exit signs [5,[26][27][28]. For enhancement of signage system performance, some researchers have studied the efficiency of signage systems according to type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on enhancing signage systems performance investigate the efficiency of signage systems according to the type, colour and design of the signage system [9,[16][17][18][19][20][21][22][23][24][25], and optimal installation location of exit signs [5,[26][27][28]. For enhancement of signage system performance, some researchers have studied the efficiency of signage systems according to type.…”
Section: Introductionmentioning
confidence: 99%
“…Frantzich and Nilsson [19] conducted experiments on three types of guidance systems in simulated situations (flashing lights, rows of flashing lights, and floor markings). Some researchers also demonstrated [20][21][22][23][24] that flash lights had a positive effect on the wayfinding of subjects through experimental studies, and conducted experimental studies of people's choices based on signage colour [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Meier et al claimed that digital emergency signage was most trusted when its information had been updated. Galea et al proposed a novel dynamic signage design and demonstrated that more than 90% of the sample could understand the purpose of new signs. Olander et al conducted a questionnaire study to investigate the design of dissuasive emergency signage and emphasized that signs that clearly negated the original exit message (eg, a red X marking across the sign) were most effective.…”
Section: Introductionmentioning
confidence: 99%
“…A key component of the IADSS is the ADSS. As part of the GETAWAY project, the ADSS was tested in a rail station to examine its effectiveness in guiding people in a full-scale evacuation trial [15], [16]. In the trial three of the four exits were considered non-viable and so had a negated exit sign located above the exits, while the fourth exit, located at the extreme end of the platform, was considered viable and had the green flashing exit sign located above the exit.…”
Section: Fig 2 Setup Of the Iadssmentioning
confidence: 99%
“…The modified sign appears as a standard emergency exit sign until the alarm is sounded, at which point the DSS is activated, hence the name Active Dynamic Signage System (ADSS). The ADSS allows an exit sign to be activated to either encourage or discourage the use of a particular route or exit [15], [16]. It is noted that the negated signage concept developed for the GETAWAY project was examined by Joakim Olander et al [17] in a later questionnaire based study.…”
Section: Introductionmentioning
confidence: 99%